Wolfenbüttelio postilė (1573) kaip seniausia lietuviška Antikos, Viduramžių ir Renesanso autorių antologija - Gelumbeckaitė, Jolanta (Literatūra, 2009)
The manuscript of the Sermon Book of Wolfenbüttel (1573) is the oldest known Lithuanian handwritten book (299 fol. 2°) and one of the largest and most important texts in the early modern history of Lithuanian. Furthermore it is a significant document of Lithuanian church and cultural history. This sermon book, consisting of sermons for an entire liturgic year, testifies the spreading of Reformation ideas and writings in the Lithuanian language area. The sermons were collected from at least ten sermon books, namely from the Postillae of Nicolaus Hemmingius, Antonius Corvinus, Johannes Spangenberg, Martin Luther, Philipp Melanchthon, Johannes Brenz, Leonhard Culmann, Arsatius Seehofer, Jodocus Willichius and Daniel Greser. Methodologically the translation is typical for the 16th century. Literally translated excerpts are followed by originally written parts, or translations from other sources are included. The Lithuanian translation is selective and paradigmatic. In many cases an (anonymous) translator takes the Latin text as a pattern according to which he creates his own sermon,or he writes an original sermon in which he includes some translated chapters. The translation is often supplemented with numerous quotations. This article deals only with part of them, in particular with those from classical authors as well as with explicit Latin citations.